Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1074/jbc.m313867200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Phospholipase A2 Translocates to Forming Phagosomes during Phagocytosis of Zymosan in Macrophages

Abstract: Resident tissue macrophages mediate early innate immune responses to microbial infection. Cytosolic phospholipase A 2 ␣ (cPLA 2 ␣) is activated in macrophages during phagocytosis of non-opsonized yeast (zymosan) triggering arachidonic acid release and eicosanoid production. cPLA 2 ␣ translocates from cytosol to membrane in response to intracellular calcium concentration ([Ca 2؉ ] i ) increases. Enhanced green fluorescent protein (EGFP)-cPLA 2 ␣ translocated to forming phagosomes, surrounding the zymosan partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 68 publications
9
74
0
Order By: Relevance
“…Taking into account the known dependency of several NADPH oxidase subunits (including gp91 phox ) on AA, we suggest that LBs may be used by phagocytes to locally release AA for NADPH oxidase activation near the phagosome. This hypothesis is strengthened by reports showing the presence of AA-releasing cPLA 2 on LBs (9) and the translocation of cPLA 2 to the phagosome in PLB-985 cells and macrophages incubated with zymosan particles (10,11). We expect that future studies with cPLA 2 -deficient PLB-985 cells, which have become available (23), may provide insight related to this hypothesis.…”
Section: Distribution Of Lbs Around Phagosomes In Wt and Gp91 Phox -Dmentioning
confidence: 63%
See 1 more Smart Citation
“…Taking into account the known dependency of several NADPH oxidase subunits (including gp91 phox ) on AA, we suggest that LBs may be used by phagocytes to locally release AA for NADPH oxidase activation near the phagosome. This hypothesis is strengthened by reports showing the presence of AA-releasing cPLA 2 on LBs (9) and the translocation of cPLA 2 to the phagosome in PLB-985 cells and macrophages incubated with zymosan particles (10,11). We expect that future studies with cPLA 2 -deficient PLB-985 cells, which have become available (23), may provide insight related to this hypothesis.…”
Section: Distribution Of Lbs Around Phagosomes In Wt and Gp91 Phox -Dmentioning
confidence: 63%
“…Arachidonic acid (AA) is the precursor for the synthesis of eicosanoids, and the enzyme that liberates AA from phospholipids upon stimulation of neutrophils and macrophages, cytosolic phospholipase A 2 (cPLA 2 ), has been colocalized with LBs (9). Interestingly, cPLA 2 recently was shown also to translocate to phagosomes in phagocytes that had ingested zymosan particles (10,11). It was found that gp91 phox (in which ''phox'' is phagocyte oxidase) is responsible for binding cPLA 2 to the phagosomal membrane (10).…”
mentioning
confidence: 99%
“…Surprisingly, human cPLA 2 -deficient cells show normal translocation of phox proteins (Dana et al, 1994;Dana et al, 1998;Shmelzer et al, 2003), suggesting cPLA 2 serves other roles in oxidase activation during Nox2 assembly. Interestingly, both cPLA 2 and secretory PLA 2 accumulate on newly formed phagosomes (Shmelzer et al, 2003;Girotti et al, 2004;Balestrieri et al, 2006). Furthermore, cells lacking Nox2 show no translocation of cPLA 2 to membranes, and it seems that human cPLA 2 associates directly with the cytoplasmic phox proteins and the membrane-bound Nox2 complex after stimulation by several agonists that activate the oxidase (Shmelzer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A number of C2-domain-containing proteins, such as PKCs, phospholipases and PI3K are known to participate in phagocytosis [37][38][39] . Though their role in phagosome closure is well documented, it is not clear whether these are also involved in the initiation.…”
Section: Discussionmentioning
confidence: 99%